Position Sensing of Wirelessly Charged Electric Personal Transporters on a Charging Pad Array - Rajan, Thomas P.; George, Boby (IECON 2022 – 48th Annual Conference of the IEEE Industrial Electronics Society, 2022)
This paper presents an efficient method to sense the position of wirelessly charged Electric Personal Transporters (EPTs) on a charging pad array to enable the right primary coil(s) to excite, ensuring high power transfer efficiency. The proposed method makes use of the impedance of the primary coil(s) at the parallel resonance frequency to sense the position of the EPT. Sensing mechanisms reported for commercially available electric vehicles like cars are not suitable in the case of EPTs, due to the huge differences in the size and shape of the vehicle structure. A study on the impedance pattern change of a circular coil charging pad array caused by wirelessly charged EPTs is conducted. Compensated coils arranged in an array or matrix format is used to form the charging pad. EPT with a tuned receiver coil modulates the input impedance measured from primary side. Impedance measurements made at the parallel resonant frequency ensures high sensitivity with respect to change in the coupling factor. While the receiver coil causes increase in primary side impedance, the metal parts, especially battery causes the impedance to fall. Single and dual coil impedance measurements of the charging array give a reliable pattern, which on analysis is used to develop an algorithm for EPT detection and positioning on the charging pad array, enabling the system to excite the coil(s) that have maximum coupling with the vehicle pad. The study conducted, the results and the algorithm presented are useful while designing and operating charging pad array for wirelessly charged EPTs even in a relatively flexible parking environment.